2008
DOI: 10.1016/j.jmb.2008.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an Fab–Protease Complex Reveals a Highly Specific Non-canonical Mechanism of Inhibition

Abstract: SummaryThe vast majority of protein protease inhibitors bind their targets in a substrate-like manner. This is a robust and efficient mechanism of inhibition, but due to the highly conserved architecture of protease active sites, these inhibitors often exhibit promiscuity. Inhibitors that show strict specificity for one protease usually achieve this selectivity by combining substrate-like binding in the active site with exosite binding on the protease surface. The development of new, specific inhibitors can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 46 publications
1
60
0
Order By: Relevance
“…Existing inhibitory antibodies against the serine protease MT-SP1 were isolated by competitively selecting for scFv in the presence of a macromolecular antigen antagonist (30). This approach yielded a steric hindrance antibody antagonist (E2) that sourced antigen specificity through MT-SP1 noncatalytic surface loops and inhibited by binding the active site (31). However, unlike D1(A12), the epitope of E2 resides within the single catalytic domain of the MT-SP1 antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Existing inhibitory antibodies against the serine protease MT-SP1 were isolated by competitively selecting for scFv in the presence of a macromolecular antigen antagonist (30). This approach yielded a steric hindrance antibody antagonist (E2) that sourced antigen specificity through MT-SP1 noncatalytic surface loops and inhibited by binding the active site (31). However, unlike D1(A12), the epitope of E2 resides within the single catalytic domain of the MT-SP1 antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Central to the detection of active matriptase, and delineation of the mechanism behind matriptase activity emerging from the epithelium, is the antibodybased probe A11. A11 is a fully human monoclonal antibody discovered previously by phage display (26). Analysis of the crystal structure of A11 bound to matriptase showed that the binding face of the antibody did not contain lysine residues (26).…”
Section: Discussionmentioning
confidence: 99%
“…A11 is a fully human monoclonal antibody discovered previously by phage display (26). Analysis of the crystal structure of A11 bound to matriptase showed that the binding face of the antibody did not contain lysine residues (26). This allows for the modification of lysine residues for imaging without abrogating the function of the antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally-occurring competitive inhibitors of protease enzymes are convex, and this appears to be a difficult geometry for the paratopes of conventional antibodies to achieve (see below): even in cases of near-true competitive inhibition, conventional antibodies use a flat or concave V H /V L interface to bind protruding regions on enzymes and partially insert one or more CDRs into the active site cleft in a non-substrate-like manner. 66,67 This hypothesis is supported by experiments using purified polyclonal immunoglobulin (Ig)Gs from enzyme-immunized dromedaries showing that competitive inhibition was a feature of heavy chain-only IgGs, but not of conventional IgGs. 11,32 It remains unclear why immunization with some enzymes yields mostly sdAbs with planar paratopes and bind outside the active site, achieving allosteric or no inhibition, although tolerance mechanisms may play a role.…”
Section: Single-domain Antibodies Directed Against Folded Proteinsmentioning
confidence: 99%